Grief Interrupted-Exploring British Muslim Communities Practices of Burial and Commemoration During Covid 19 - Rashida Bibi (SAGE Open)
This paper focuses on death, in particular it discusses experiences of burial, grief and commemoration for British Muslim communities during Covid 19. The paper considers the impact of Covid 19 on British Muslim communities through a phenomenological and socio-cultural lens and discusses ways in which religious and cultural practices inherent to the Muslim faith, including washing and shrouding of the deceased, were particularly affected by Covid 19. Drawing on ritual studies and the concept of liminality, the paper discusses the social and relational aspect of religious rituals as important in facilitating the processes of grief and bereavement. The empirical discussion in this paper is drawn from interviews with British Muslims working or volunteering with ethnic minority communities, including medical professionals, funeral directors and burial charities who had direct experience of both preparing Muslim bodies for burial and supporting bereaved families. The paper discusses ways in which rituals function in the social cohesiveness of communities, and ‘glue’ a community together particularly at a time when it is most threatened. In considering the disruptions to the collective and communal rituals related to death, burial and mourning the British Muslim community, the paper discusses ways in which these disruptions have contributed to a sense of lingering grief or grief ‘interrupted’.